An adsorbent intermediate carrier with core-shell structure and its preparation method and application

By grafting polyglycidyl methacrylate on carbon balls prepared by biomass waste or biodegradable plastics to form an adsorbent intermediate carrier with a core-shell structure, the existing adsorbent cost and insufficient adsorption capacity are solved. The problem is that the adsorption rate and high capacity are achieved, and the advantages of green and environmental protection are achieved.

CN116422292BActive Publication Date: 2024-12-24GUIZHOU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310428313.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-20
Publication Date
2024-12-24
Estimated Expiration
2043-04-20

AI Technical Summary

Technical Problem

Among the existing adsorbents, activated carbon and carbon materials are costly and have poor adsorption capacity for metal ions. The surface functional groups of hydrothermal carbon balls are many but the adsorption capacity is poor. The graft polymerization reaction caused by cerium salt is mainly limited to water solubility. Substrate, lacks application for hydrothermal carbon spheres.

Method used

Use biomass waste or biodegradable plastic as carbon source to prepare carbon balls by hydrothermal carbonization, and graft polyglycidyl methacrylate as shell material on the carbon balls to form the adsorbent middle of the core-shell structure The carrier increases the epoxy content on its surface, facilitates functional modification, and enhances adsorption rate and capacity.

Benefits of technology

The adsorbent surface is rich in epoxy groups, simplifies functional modification, improves adsorption rate and capacity. At the same time, the use of biomass materials reduces costs and has the advantage of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004189425450000121
    Figure BDA0004189425450000121
Patent Text Reader

Abstract

The present invention provides an adsorbent intermediate carrier with a core-shell structure, a preparation method and an application thereof, wherein the core of the core-shell structure is a carbon ball, the material of the shell layer includes poly(glycidyl methacrylate), and the carbon source of the carbon ball is biomass waste and / or biodegradable plastic. By grafting poly(glycidyl methacrylate) onto the carbon ball with biomass waste and / or biodegradable plastic as the carbon source, the surface of the obtained adsorbent intermediate carrier is rich in epoxy groups, thereby facilitating the subsequent functional modification of ligands and ensuring that the adsorbent obtained after the functional modification of the ligands has the advantages of fast adsorption rate and high adsorption capacity. At the same time, because the carbon source is biomass waste and / or biodegradable plastic, the adsorbent intermediate carrier also has the advantages of wide source, low cost and green environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbents, and in particular relates to an adsorbent intermediate carrier with a core-shell structure and a preparation method and application thereof. Background Art

[0002] There are many types of adsorbent materials, which can be roughly divided into two categories: inorganic materials and adsorbent resins. Inorganic material-based adsorbents often have excellent stability and mechanical strength, and almost no swelling phenomenon, and are an excellent adsorbent or adsorbent carrier; among them, carbon adsorption materials have a long history, and new carbon materials emerge in an endless stream, such as activated carbon, carbon tubes, carbon balls, fullerenes, graphene, etc.; activated carbon has strong adsorption capacity for non-polar substances but generally has low adsorption capacity for metal ions. The preparation of activated carbon requires high temperature conditions isolated from air and is difficult to regenerate, so the cost is relatively high; in addition to activated carbon, carbon materials such as carbon tubes, graphene, and carbon molecular sieves have also been used as adsorption materials by people, but the preparation cost of such carbon materials is high and is still in the laboratory research stage.

[0003] In recent years, a new method of preparing various monodisperse nano / micro carbon spheres by hydrothermal carbonization technology using various carbon-containing biomass (such as glucose, sucrose, starch and other sugars) as carbon sources has begun to attract widespread attention. This is a simple, cheap, low-energy and universal method for synthesizing carbon materials. In addition, the synthesized carbon spheres have regular morphology, controllable size, and very high content of surface active functional groups (such as hydroxyl groups), some of which can be as high as 50% or more, and can be used as precursors or basic materials for synthesizing other complex structural materials. There are more and more reports on the preparation of hydrothermal carbon spheres by hydrothermal carbonization technology using carbon-containing biomass such as sugars as carbon sources. The carbon materials synthesized by this method have been widely applied in the fields of energy, catalysis and preparation of various composite microspheres, and have gradually extended to the environmental field. However, there is almost no literature on the preparation of hydrothermal carbon spheres rich in hydroxyl groups using waste carbon-containing materials as carbon sources; and although there are many functional groups on the surface of hydrothermal carbon spheres, their adsorption capacity for many substances such as metal ions is not ideal. Therefore, it is very necessary to use necessary chemical modification methods to functionalize the surface of hydrothermal carbon balls to improve their adsorption and separation performance for rare earth ions.

[0004] Adsorption resin is a porous spatial network-like polymer formed by polymerizing or condensing organic compound monomer molecules. Adsorption resins used in metal separation usually have active ligands that can exchange or complex with metal ions. In the separation industry, this kind of polymer material with special functions is usually called ion exchange resin, which is widely used in metal element separation, purification and impurity removal of various solutions, etc. Modern ion exchange resins are mostly prepared from petroleum products as raw materials. They have the advantages of high adsorption capacity, insolubility in acid / alkali, high stability, and wide application range. Among them, poly(glycidyl methacrylate) (PGMA) adsorption resin is also an excellent adsorbent. Because it contains a large number of epoxy groups, it is easy to modify various functional ligands through ring-opening reactions, and has good application prospects in adsorbent carriers, catalyst carriers, drugs and gene carriers. However, the raw materials and synthesis costs of organic adsorption resins are relatively high, and the hydraulic properties and mechanical properties are poor. For example, the resin is easy to swell, and the compression and wear resistance needs to be further improved.

[0005] Cerium salt (Ce 4+ )-induced grafting polymerization reaction has a wide range of applications in the surface modification and modification of natural or synthetic polymers such as cellulose, starch, polyvinyl alcohol, etc. [. 4+ The necessary condition for initiating graft polymerization is that the grafted substrate must contain active hydroxyl or thiol functional groups to allow Ce 4+ Oxidation reactions occur on it to produce free radicals. Compared with other carbon materials, the biggest advantage of hydrothermal carbon spheres is that they contain abundant oxygen-containing functional groups on the surface. The mass of some oxygen-containing functional groups can account for more than 50% of the total mass of carbon spheres, and their hydroxyl content is much higher than other carbon materials. However, the grafting polymerization reactions initiated by cerium salts are currently limited to water-soluble substrates (such as cellulose, starch, polyvinyl alcohol, etc.), and there are almost no reports on grafting polymerization reactions on the surface of hydrothermal carbon spheres.

[0006] Therefore, developing an adsorbent intermediate carrier with carbon spheres as the core and poly(glycidyl methacrylate) as the shell is a technical problem that needs to be urgently solved in this field. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide an adsorbent intermediate carrier with a core-shell structure, a preparation method and an application thereof, wherein the adsorbent intermediate carrier is a core-shell structure, the core of which is a carbon sphere, the carbon source of the carbon sphere is biomass waste and / or biodegradable plastic, the material of the shell layer includes poly(glycidyl methacrylate), and the surface of the obtained adsorbent intermediate carrier is rich in epoxy groups by grafting poly(glycidyl methacrylate) as a shell material onto the carbon sphere with biomass waste and / or biodegradable plastic as a carbon source, thereby facilitating the subsequent functional modification of ligands and ensuring that the adsorbent obtained after the functional modification of the ligands has the advantages of fast adsorption rate and high adsorption capacity.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides an adsorbent intermediate carrier having a core-shell structure, wherein the core of the core-shell structure is a carbon sphere, and the material of the shell layer includes poly(glycidyl methacrylate);

[0010] The carbon source of the carbon balls is biomass waste and / or biodegradable plastic.

[0011] The adsorbent intermediate carrier provided by the present invention has a core-shell structure, the core of the core-shell structure is a carbon ball, the carbon source of the carbon ball is biomass waste and / or biodegradable plastic, and the shell material of the core-shell structure includes poly(glycidyl methacrylate); the present invention grafts poly(glycidyl methacrylate) as a shell material onto a carbon ball with biomass waste and / or biodegradable plastic as a carbon source, so that the surface of the obtained adsorbent intermediate carrier is rich in epoxy groups, and the ring-opening reaction of the epoxy group can be conveniently introduced with a variety of target functional ligands, such as amino, thiol, carboxyl, etc., so that the adsorbent intermediate carrier is convenient for subsequent functional modification of ligands, and it can be ensured that the adsorbent obtained after the functional modification of the ligand has the advantages of fast adsorption rate and high adsorption capacity; at the same time, because the carbon source of the carbon ball is biomass waste and / or biodegradable plastic, it has the advantages of wide source, low cost and green environmental protection.

[0012] Preferably, the particle size of the carbon spheres is 0.1 to 10 μm, for example, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or 9 μm.

[0013] Preferably, the carbon spheres are obtained by hydrothermal carbonization of biomass waste and / or biodegradable plastics.

[0014] As a preferred technical solution of the present invention, a hydrothermal method is used to carbonize the carbon source, so that hydrothermal carbon balls with controllable size, dispersion and number of hydroxyl groups can be synthesized.

[0015] Preferably, the biomass waste includes any one of corn straw, rice straw, wheat straw, wheat bran, rice husk, corn cob, tea residue, sugarcane bagasse, fruit peel, waste paper products or waste cotton and linen products, or a combination of at least two of them.

[0016] Preferably, the biodegradable plastic comprises any one of polylactic acid, polybutylene succinate or polyglycolic acid, or a combination of at least two thereof.

[0017] Preferably, the poly(glycidyl methacrylate) is grafted onto the carbon sphere, and the grafting rate of the poly(glycidyl methacrylate) onto the carbon sphere is 5-90%, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70% or 80%, etc.

[0018] In a second aspect, the present invention provides a method for preparing the adsorbent intermediate carrier as described in the first aspect, the preparation method comprising the following steps:

[0019] (1) hydrothermally carbonizing biomass waste and / or biodegradable plastic to obtain carbon balls;

[0020] (2) subjecting the carbon spheres obtained in step (1) to an alkalization treatment to obtain alkalized carbon spheres;

[0021] (3) reacting the alkalized carbon spheres obtained in step (2), an initiator and glycidyl methacrylate to obtain the adsorbent intermediate carrier.

[0022] The preparation method of the adsorbent intermediate carrier provided by the present invention firstly uses biomass waste and / or biodegradable plastic as a carbon source for hydrothermal carbonization to obtain carbon balls. Specifically, the biomass waste and / or biodegradable plastic can be mixed with water, wherein the soluble carbon source is directly dissolved in water to form a uniform solution, and the insoluble carbon source is formed into micropowder and then dispersed in water to form a solid suspension; then the obtained carbon balls are subjected to alkalization treatment. The purpose of the alkalization treatment is to make the carbon balls swell and then destroy the hydrogen bond structure inside the carbon balls, so that the bound hydroxyl groups are more exposed, and the accessibility of the functional groups is effectively improved. This step is not only conducive to improving the adsorption capacity of the adsorbent intermediate carrier to metal ions after the adsorbent is formed, but also conducive to further improving the PGMA on the surface of the carbon balls. The grafting rate can increase the content of active functional groups (epoxy groups) on the surface of the final adsorbent intermediate; finally, the GMA monomer is polymerized and grafted on the carbon sphere after alkali treatment by the initiator grafting method. This grafting method not only makes the epoxy group content on the surface of the adsorbent intermediate much higher than the epoxy group content grafted by the ordinary chemical modification method, but also the chain length and grafting rate of the grafted PGMA can be controlled by adjusting the amount of GMA monomer, the amount of initiator, the concentration of the initiator, the polymerization temperature and other reaction conditions; the obtained waste biomass adsorbent active intermediate carrier grafted with "whisker-like" PGMA polymer chains is convenient for subsequent functional modification when used as an adsorbent, and the adsorbent obtained after functional modification also has the advantages of fast adsorption rate and high adsorption capacity.

[0023] Preferably, step (1) further includes a step of pretreating the biomass waste and / or biodegradable plastic before the hydrothermal carbonization.

[0024] Preferably, the pretreatment comprises the steps of crushing, screening, alkali washing, acid washing, water washing and drying.

[0025] Preferably, the hydrothermal carbonization method in step (1) specifically comprises: dissolving biomass waste and / or organisms in water for carbonization treatment to complete the hydrothermal carbonization.

[0026] Preferably, in the process of dissolving biomass waste and / or waste organisms in water for carbonization treatment, the mass concentration of biomass waste and / or waste organisms in water is 30 to 300 g / L, for example, 50 g / L, 100 g / L, 150 g / L, 200 g / L, 250 g / L or 300 g / L, and more preferably 60 to 180 g / L.

[0027] Preferably, the hydrothermal carbonization in step (1) is carried out in a stainless steel hydrothermal reactor lined with polytetrafluoroethylene.

[0028] Preferably, the filling degree of the stainless steel hydrothermal reactor is 40-90%, such as 45%, 50%, 55%, 60%, 70% or 80%, and more preferably 60-80%.

[0029] Preferably, the temperature of the carbonization treatment is 150-250°C, for example, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, and more preferably 180-220°C.

[0030] Preferably, the carbonization treatment time is 2 to 72 hours, for example, 5 hours, 10 hours, 20 hours, 30 hours, 40 hours, 50 hours, 60 hours or 70 hours, and more preferably 12 to 24 hours.

[0031] Preferably, after the hydrothermal carbonization in step (1), the steps of cooling to room temperature, centrifugal separation and washing are also included.

[0032] Preferably, the alkalization treatment method in step (2) specifically comprises: mixing the carbon spheres obtained in step (1) with an alkaline aqueous solution to complete the alkalization treatment.

[0033] Preferably, the solid-liquid ratio of the carbon spheres and the alkaline aqueous solution is g:mL 1:(5-150), for example, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:50, 1:70 or 1:90, etc.

[0034] Preferably, the alkaline aqueous solution comprises an aqueous sodium hydroxide solution.

[0035] Preferably, based on the volume of the sodium hydroxide aqueous solution as 1 L, the molar number of the sodium hydroxide is 0.1 to 5 mol, such as 0.5 mol, 1 mol, 2 mol, 3 mol or 4 mol, etc., and more preferably 0.5 to 2 mol / L.

[0036] Preferably, the mixing temperature is 20-100°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or 90°C, and more preferably 40-50°C.

[0037] Preferably, the mixing time is 1 to 48 hours, for example, 5 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours or 45 hours, and more preferably 6 to 24 hours.

[0038] Preferably, the initiator in step (3) comprises a cerium salt.

[0039] Preferably, the cerium salt comprises ammonium cerium nitrate.

[0040] It should be noted that in actual operation, ammonium cerium nitrate needs to be dissolved in a nitric acid solution to obtain ammonium cerium nitrate and a nitric acid solution.

[0041] Preferably, the concentration of ammonium cerium nitrate in the nitric acid solution of ammonium cerium nitrate is 0.005-0.5 mol / L, for example, 0.007 mol / L, 0.009 mol / L, 0.11 mol / L, 0.13 mol / L, 0.15 mol / L, 0.1 mol / L or 0.3 mol / L, and more preferably 0.05-0.5 mol / L.

[0042] Preferably, the concentration of nitric acid in the nitric acid solution is 0.01-5 mol / L, for example, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L or 4 mol / L.

[0043] Preferably, the reaction in step (3) is carried out under protective gas conditions, more preferably under nitrogen conditions.

[0044] Preferably, the reaction temperature in step (3) is 50-100°C, such as 60°C, 70°C, 80°C or 90°C, and more preferably 60-70°C;

[0045] Preferably, the reaction time of step (3) is 2 to 24 h, such as 5 h, 10 h, 15 h or 20 h, and more preferably 4 to 8 h.

[0046] As a preferred technical solution of the present invention, the preparation method of the adsorbent intermediate carrier specifically comprises the following steps:

[0047] (1a) pulverizing, screening, washing and drying the biomass waste and / or biodegradable plastic in sequence to obtain pretreated biomass waste and / or biodegradable plastic;

[0048] (1b) subjecting the pretreated biomass waste and / or biodegradable plastic obtained in step (1a) to hydrothermal carbonization in water at a temperature of 150 to 250° C. for 2 to 72 hours to obtain carbon balls;

[0049] (2) mixing the carbon spheres obtained in step (1b) with an alkaline aqueous solution at 40 to 50° C. for 2 to 48 hours, filtering, washing, and drying to obtain alkalized carbon spheres;

[0050] (3) Under protective gas protection conditions, the alkalized carbon spheres obtained in step (2) are mixed with water, an initiator and glycidyl methacrylate are added, the mixture is reacted at 50 to 100° C. for 2 to 24 hours, and washed to obtain the adsorbent intermediate carrier.

[0051] In a third aspect, the present invention provides an adsorbent, comprising the adsorbent intermediate carrier and a ligand as described in the first aspect.

[0052] Preferably, the ligand comprises any one of an amine-containing ligand, a thiol-containing ligand or an anhydride-containing ligand, or a combination of at least two thereof.

[0053] Preferably, the ligand comprises any one of ethylenediamine, polyethyleneimine, thiosemicarbazide, thiol, ethanedithiol, succinic anhydride or succinic anhydride, or a combination of at least two thereof.

[0054] In a fourth aspect, the present invention provides a use of the adsorbent as described in the third aspect in hydrometallurgy or wastewater treatment.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] The core of the adsorbent intermediate carrier with a core-shell structure provided by the present invention is a carbon ball, the carbon source of the carbon ball is biomass waste and / or biodegradable plastic, and the shell material of the core-shell structure includes poly(glycidyl methacrylate); by grafting poly(glycidyl methacrylate) as a shell material onto the carbon ball with biomass waste and / or biodegradable plastic as a carbon source, the surface of the adsorbent intermediate carrier with a core-shell structure is rich in epoxy groups, so that the adsorbent intermediate carrier is convenient for subsequent functional modification, and it can be ensured that the adsorbent obtained after the functional modification has the advantages of fast adsorption rate and high adsorption capacity; at the same time, because the carbon ball is obtained by carbonizing biomass waste and / or biodegradable plastic, it has the advantages of wide source, low cost and green environmental protection. DETAILED DESCRIPTION

[0057] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] Example 1

[0059] An adsorbent intermediate carrier with a core-shell structure, wherein the core of the core-shell structure is a carbon ball obtained by hydrothermal carbonization using corn stalks as a carbon source, and the material of the shell layer includes poly(glycidyl methacrylate);

[0060] The preparation method thereof comprises the following steps:

[0061] (1) crushing, screening, washing and drying the corn stalks in sequence to obtain pretreated corn stalk powder;

[0062] (2) Accurately weigh 6.4 g of the pretreated corn stalk powder obtained in step (1) and add it to water to obtain a solid suspension with a corn stalk mass concentration of 80 g / L. The solid suspension is transferred to a stainless steel hydrothermal reactor with a volume of 0.1 L and a polytetrafluoroethylene lining (filling degree is 80%). The stainless steel hydrothermal reactor is placed in a constant temperature reactor, and the temperature is slowly raised to 200° C. and the reaction is carried out at a constant temperature for 24 hours. After the reaction is completed, the product is naturally cooled to room temperature. A black solid product is generated, which is centrifuged and washed with water and ethanol several times. The collected black solid is vacuum dried in a vacuum drying oven to obtain carbon spheres.

[0063] (3) placing the carbon spheres obtained in step (2) and a sodium hydroxide aqueous solution (the concentration of sodium hydroxide is 0.5 mol / L) in a 40°C constant temperature water bath oscillator (speed 100 rpm) at a solid-liquid ratio (g:mL) of 1:100 and mixing at a constant temperature for 6 hours, centrifuging, washing with water until nearly neutral and drying to obtain alkalized carbon spheres;

[0064] (4) Add the alkaline carbon balls obtained in step (3) and deionized water at a solid-liquid ratio (g:mL) of 1:800 into the reactor, place the reactor in a constant temperature water bath oscillator at 60°C (speed of 100 rpm), continuously pass nitrogen gas for deoxygenation, add 10 mL of ammonium cerium nitrate solution pre-dissolved in nitric acid solution (the concentration of ammonium cerium nitrate is 0.1 mol / L, and the concentration of nitric acid is 1 mol / L) and 10 mL of glycidyl methacrylate, react at 60°C for 6 hours, wash and dry to obtain the adsorbent intermediate carrier with a core-shell structure.

[0065] Example 2

[0066] An adsorbent intermediate carrier with a core-shell structure, wherein the core of the core-shell structure is a carbon sphere obtained by hydrothermal carbonization using polybutylene succinate as a carbon source, and the material of the shell layer includes polyglycidyl methacrylate;

[0067] The preparation method thereof comprises the following steps:

[0068] (1) Accurately weigh 2.7 g of polybutylene succinate (CAS code: 25777-14-4) and add it to water to obtain a solution with a mass concentration of 90 g / L of polybutylene succinate. The above solution is transferred to a stainless steel hydrothermal reactor with a volume of 0.1 L and a polytetrafluoroethylene lining (filling degree is 60%). The above stainless steel hydrothermal reactor is placed in a constant temperature reactor, and the temperature is slowly raised to 220° C. and the reaction is carried out at a constant temperature for 12 hours. After the reaction is completed, it is naturally cooled to room temperature. A black solid product is generated, which is centrifuged and washed with water and ethanol several times. The collected black solid is vacuum dried in a vacuum drying oven to obtain carbon spheres;

[0069] (2) the carbon spheres obtained in step (1) and a sodium hydroxide aqueous solution (the concentration of sodium hydroxide is 1 mol / L) are oscillated at a constant temperature for 2 h at a solid-liquid ratio (g:mL) of 1:50, centrifuged, washed with water until nearly neutral and dried to obtain alkalized carbon spheres;

[0070] (3) Add the alkaline carbon balls obtained in step (2) and deionized water at a solid-liquid ratio (g:mL) of 1:75 into the reactor, place the reactor in a constant temperature water bath at 80°C, continuously pass nitrogen to deoxygenate, add 8mL of ammonium cerium nitrate solution pre-dissolved in nitric acid solution (the concentration of ammonium cerium nitrate is 0.1mol / L, and the concentration of nitric acid is 1mol / L) and 15mL of glycidyl methacrylate, react at 80°C for 4h, wash and dry to obtain the adsorbent intermediate carrier.

[0071] Example 3

[0072] An adsorbent intermediate carrier with a core-shell structure, which differs from Example 1 only in that the reaction temperature of step (4) is 70° C. and the reaction time is 24 h. Other substances, steps and parameters are the same as those in Example 1.

[0073] Example 4

[0074] An adsorbent intermediate carrier with a core-shell structure, which differs from Example 1 only in that the reaction temperature of step (4) is 100° C. and the reaction time is 2 h. Other substances, steps and parameters are the same as those in Example 1.

[0075] Comparative Example 1

[0076] An adsorbent intermediate carrier with a core-shell structure, wherein the core is a carbon ball obtained by hydrothermal carbonization of corn stalks, and the material of the shell layer includes poly(glycidyl methacrylate);

[0077] The preparation method thereof comprises the following steps:

[0078] (1) crushing, screening, washing and drying the corn stalks in sequence to obtain pretreated corn stalk powder;

[0079] (2) Accurately weigh 4.32 g of the corn straw powder pretreated in step (1) and add it to water to obtain a solid suspension with a mass concentration of 54 g / L of corn straw. The solid suspension is transferred to a stainless steel hydrothermal reactor with a volume of 0.1 L and a polytetrafluoroethylene lining (filling degree is 80%), placed in a constant temperature reactor, and slowly heated to 200° C. and reacted at a constant temperature for 20 h. After the reaction is completed, it is naturally cooled to room temperature to generate a black solid product, which is centrifuged and washed several times with water and ethanol. The collected black solid is vacuum dried in a vacuum drying oven to obtain carbon spheres.

[0080] (3) Add the carbon balls obtained in step (2) and deionized water at a solid-liquid ratio (g:mL) of 1:80 into the reactor, place the reactor in a constant temperature water bath at 65°C, continuously pass nitrogen to deoxygenate, add 10mL of ammonium cerium nitrate solution pre-dissolved in nitric acid solution (the concentration of ammonium cerium nitrate is 0.1 mol / L, and the concentration of nitric acid is 1 mol / L) and 10mL of glycidyl methacrylate, react at 65°C for 6h, wash and dry to obtain the adsorbent intermediate carrier.

[0081] Performance Testing:

[0082] The adsorbent intermediate carrier obtained in Examples 1 to 4 and Comparative Example 1 and 10% by weight of polyethyleneimine (number average molecular weight of 10,000) were mixed at 80° C. for 6 hours to obtain an adsorbent, and the following tests were performed;

[0083] (1) N content: the content of N in the test adsorbent, in mmol / g;

[0084] (2) Adsorption rate: Add the adsorbent to a certain concentration of Pt(IV) solution, take samples at different times, test the Pt(IV) concentration in the solution, calculate the adsorption amount of Pt(IV) at different times and draw a kinetic adsorption curve to obtain the time taken to reach adsorption equilibrium;

[0085] (3) Saturated adsorption capacity: The adsorbent was added to Pt(IV) solutions of different concentrations. After adsorption equilibrium, the Pt(IV) concentration in the solution was tested. The equilibrium adsorption amount of Pt(IV) in the starting Pt(IV) solutions of different concentrations was calculated and the thermodynamic adsorption equilibrium curve was plotted to obtain the saturated adsorption capacity of Pt(IV).

[0086] The adsorbent intermediate carrier with a core-shell structure provided by Examples 1 to 4 and Comparative Example 1 was tested according to the above test method. The test results are shown in Table 1:

[0087] Table 1

[0088]

[0089] According to the data in Table 1, we can see that:

[0090] The content of N element in the adsorbent obtained by combining the adsorbent carrier provided in Examples 1 to 4 with ammonium ion ligands is 4 to 5.9 mmol / g, indicating that the ligand grafting rate is relatively high; the time to reach adsorption equilibrium is 10 minutes, indicating that the adsorption rate is relatively fast; the adsorption amount for Pt(IV) can reach 2.2 to 3.3 mmol / g, indicating that the adsorption amount is relatively high.

[0091] However, the adsorbent obtained by combining the adsorbent intermediate carrier provided in Comparative Example 1 without alkalization with the ammonium ion ligand has a low ligand grafting rate, and thus a poor adsorption effect.

[0092] The applicant declares that the present invention illustrates an adsorbent intermediate carrier with a core-shell structure and its preparation method and application through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An adsorbent intermediate carrier having a core-shell structure, characterized in that: The core of the core-shell structure is a carbon sphere, and the material of the shell layer includes poly(glycidyl methacrylate); The carbon source of the carbon balls is biomass waste and / or biodegradable plastic; The adsorbent intermediate carrier is prepared by the following method, which comprises: (1) hydrothermally carbonizing biomass waste and / or biodegradable plastic to obtain carbon balls; (2) treating the carbon spheres obtained in step (1) with an alkalization agent to obtain alkalized carbon spheres; (3) reacting the alkalized carbon spheres obtained in step (2), an initiator and glycidyl methacrylate to obtain the adsorbent intermediate carrier; The initiator includes a cerium salt.

2. The adsorbent intermediate carrier according to claim 1, characterized in that: The particle size of the carbon spheres is 0.1-10 μm.

3. The adsorbent intermediate carrier according to claim 1, characterized in that: The biomass waste includes any one of corn straw, rice straw, wheat straw, wheat bran, rice husk, corn cob, tea residue, sugarcane bagasse, fruit peel, waste paper products or waste cotton and linen products, or a combination of at least two of them.

4. The adsorbent intermediate carrier according to claim 1, characterized in that: The biodegradable plastic includes any one of polylactic acid, polybutylene succinate or polyglycolic acid or a combination of at least two thereof.

5. The adsorbent intermediate carrier according to claim 1, characterized in that: The poly(glycidyl methacrylate) is grafted onto the carbon sphere, and the grafting rate of the poly(glycidyl methacrylate) onto the carbon sphere is 5-90%.

6. A method for preparing the adsorbent intermediate carrier according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) hydrothermally carbonizing biomass waste and / or biodegradable plastic to obtain carbon balls; (2) treating the carbon spheres obtained in step (1) with an alkalization agent to obtain alkalized carbon spheres; (3) reacting the alkalized carbon spheres obtained in step (2), an initiator and glycidyl methacrylate to obtain the adsorbent intermediate carrier; The initiator includes a cerium salt.

7. The preparation method according to claim 6, characterized in that: Step (1) also includes a step of pre-treating the biomass waste and / or biodegradable plastic before the hydrothermal carbonization.

8. The preparation method according to claim 7, characterized in that: The pretreatment includes the steps of crushing, screening, alkali washing, acid washing, water washing and drying.

9. The preparation method according to claim 6, characterized in that: The hydrothermal carbonization method in step (1) specifically comprises: dissolving the biomass waste and / or biodegradable plastic in water for carbonization treatment to complete the hydrothermal carbonization.

10. The preparation method according to claim 9, characterized in that: The temperature of the carbonization treatment is 150-250°C.

11. The preparation method according to claim 10, characterized in that: The temperature of the carbonization treatment is 180-220°C.

12. The preparation method according to claim 9, characterized in that: The carbonization treatment time is 2 to 72 h.

13. The preparation method according to claim 12, characterized in that: The carbonization treatment time is 12 to 24 hours.

14. The preparation method according to claim 6, characterized in that: The alkalization treatment method in step (2) specifically comprises: mixing the carbon spheres obtained in step (1) with an alkaline aqueous solution to complete the alkalization treatment.

15. The preparation method according to claim 14, characterized in that: The alkaline aqueous solution includes an aqueous sodium hydroxide solution.

16. The preparation method according to claim 14, characterized in that: The mixing temperature is 20-100°C.

17. The preparation method according to claim 16, characterized in that: The mixing temperature is 40-50°C.

18. The preparation method according to claim 14, characterized in that: The mixing time is 2 to 48 hours.

19. The preparation method according to claim 18, characterized in that: The mixing time is 6 to 24 hours.

20. The preparation method according to claim 6, characterized in that: The cerium salt includes ammonium cerium nitrate.

21. The preparation method according to claim 6, characterized in that: The reaction in step (3) is carried out under protective gas protection conditions.

22. The preparation method according to claim 21, characterized in that: The reaction in step (3) is carried out under nitrogen protection.

23. The preparation method according to claim 6, characterized in that: The reaction temperature in step (3) is 50-100°C.

24. The preparation method according to claim 23, characterized in that: The reaction temperature in step (3) is 60-70°C.

25. The preparation method according to claim 6, characterized in that: The reaction time of step (3) is 2 to 24 h.

26. The preparation method according to claim 25, characterized in that: The reaction time of step (3) is 4 to 8 h.

27. The preparation method according to claim 6, characterized in that: The preparation method specifically comprises the following steps: (1a) pulverizing, screening, washing and drying the biomass waste and / or biodegradable plastic in sequence to obtain pretreated biomass waste and / or biodegradable plastic; (1b) subjecting the pretreated biomass waste and / or biodegradable plastic obtained in step (1a) to hydrothermal carbonization at a temperature of 150 to 250° C. for a time of 2 to 72 h to obtain carbon balls; (2) mixing the carbon spheres obtained in step (1b) with an alkaline aqueous solution at 40-50° C. for 2-48 h, filtering, washing, and drying to obtain alkalized carbon spheres; (3) Under protective gas conditions, the alkalized carbon spheres obtained in step (2) are mixed with water, an initiator and glycidyl methacrylate are added, the mixture is reacted at 50-100° C. for 2-24 h, and washed to obtain the adsorbent intermediate carrier.

28. An adsorbent, characterized in that The adsorbent comprises the adsorbent intermediate carrier and the ligand as described in any one of claims 1 to 5.

29. The adsorbent according to claim 28, characterized in that The ligand includes any one of an amine-containing ligand, a thiol-containing ligand or an anhydride-containing ligand, or a combination of at least two of them.

30. The adsorbent according to claim 29, characterized in that The ligand includes any one of ethylenediamine, polyethyleneimine, thiosemicarbazide, thiol, ethanedithiol, succinic anhydride or succinic anhydride, or a combination of at least two thereof.

31. Use of the adsorbent according to any one of claims 28 to 30 in hydrometallurgy or wastewater treatment.